Disrupted microsaccade responses in late-life depression - Lee, Yao-Tung (2025)
Late-life depression (LLD) is a psychiatric disorder in older adults, characterized by high prevalence and significant mortality rates. Thus, it is imperative to develop objective and cost-effective methods for detecting LLD. Individuals with depression often exhibit disrupted levels of arousal, and microsaccades, as a type of fixational eye movement that can be measured non-invasively, are known to be modulated by arousal. This makes microsaccades a promising candidate as biomarkers for LLD. In this study, we used a high-resolution, video-based eye-tracker to examine microsaccade behavior in a visual fixation task between LLD patients and age-matched healthy controls (CTRL). Our goal was to determine whether microsaccade responses are disrupted in LLD compared to CTRL. LLD patients exhibited significantly higher microsaccade peak velocities and larger amplitudes compared to CTRL. Although microsaccade rates were lower in LLD than in CTRL, these differences were not statistically significant. Additionally, while both groups displayed microsaccadic inhibition and rebound in response to changes in background luminance, this modulation was significantly blunted in LLD patients, suggesting dysfunction in the neural circuits responsible for microsaccade generation. Together, these findings, for the first time, demonstrate significant alterations in microsaccade behavior in LLD patients compared to CTRL, highlighting the potential of these disrupted responses as behavioral biomarkers for identifying individuals at risk for LLD.